The nurse's perspective on the low-risk pregnancy and puerperal cycle (Research, Society and Development, 2024)
The nurse in prenatal care has the role of providing adequate quality in the care of pregnant women, ensuring that the development of the pregnancy occurs in an effective and healthy manner, without presenting risks to the mother and the baby. Objective: To understand the role of the nurse in the low-risk pregnancy-puerperal cycle. Methodology: This is a research developed using the bibliographic review method. It aimed to analyze 10 articles published online in the Scientific Electronic Library Online (SciELO) Database. Result: The nurse performs functions such as: monitoring, assistance, humanized care and health promotion during this period, emphasizing mainly the care of the newborn. This professional and his/her team offer actions that create the emotional bond that minimizes errors and complications in the nursing diagnosis. Final Considerations: This study sought to deepen the role of the nurse in the pregnancy-puerperal cycle. It was identified through bibliographic reviews that it is of fundamental importance for pregnant women to adhere to the care provided by nurses. It is up to the nurse to carry out educational actions covering their entire community, involving the team, in order to increase the coverage rates of prenatal monitoring in Primary Care.